Transcranial Direct Current Stimulation Enhances Muscle Strength of Non-dominant Knee in Healthy Young Males - Lu, Panpan; Hanson, Nicholas J.; Wen, Lin; Guo, Feng; Tian, Xiaoyu (Frontiers in Physiology, 2021)
Transcranial direct current stimulation (tDCS) has been applied in training and competition, but its effects on physical performance remain largely unknown. The present study aimed to observe the effect of tDCS on muscular strength and knee activation. Nineteen healthy young males were subjected to 20 min of real stimulation (2 mA) and sham stimulation (0 mA) over the primary motor cortex (M1) bilaterally on different days. The maximal voluntary contraction (MVC) of the knee extensors and flexors, as well as surface electromyography (sEMG) of the rectus femoris (RF) and biceps femoris (BF) were recorded before, immediately after, and 30 min after stimulation. MVC, rate of force development (RFD), and sEMG activity were analyzed before and after each condition. MVC of the non-dominant leg extensor and flexor was significantly higher immediately after real stimulation and 30 min after stimulation than before, and MVC of the non-dominant leg flexor was significantly higher 30 min after real stimulation than that after sham stimulation (P < 0.05). The RFD of the non-dominant leg extensor and flexor immediately after real stimulation was significantly higher than before stimulation, and the RFD of the non-dominant leg extensor immediately after real stimulation and 30 min after stimulation was significantly higher than that of sham stimulation (P < 0.05). EMG analysis showed the root mean square (RMS) amplitude and mean power frequency (MPF) of the non-dominant BF and RF were significantly higher immediately after real stimulation and 30 min after stimulation than before stimulation, and the MPF of the non-dominant BF EMG was significantly higher 30 min after real stimulation than that after sham stimulation (P < 0.05). Bilateral tDCS of the primary motor cortex can significantly improve the muscle strength and explosive force of the non-dominant knee extensor and flexor, which might result from an increased recruitment of motor units. This effect can last until 30 min after stimulation, but there is no significant effect on the dominant knee.